Analysis of Organizational Performance and Community Satisfaction in Increasing Public Trust (Case Study: Population and Civil Registry Service in Malang Regency) - Anggelina Afrilia Nurjannah (JURNAL INOVASI SAINS TEKNOLOGI DAN BISNIS, 2023)
An analysis of organizational performance and community satisfaction in relation to boosting public trust in the Malang Regency’s Department of Population and Civil Registry was the goal of this study. The data collection method starts with modeling the relationship between constructs, creating a questionnaire, and disseminating it. Next, data is processed using SPPS and SmartPLS, and then the findings of the relationship between constructs are read. This kind of study uses a causalistic descriptive methodology and is quantitative. The authors used this model to carry out research using structural equation modeling. The study’s findings indicated that the effectiveness of an organization’s human resources positively impacts service quality by about 70%, organizational performance by about 83%, and public trust by about 34%. Service excellence increases public trust by about 40% and corporate performance by about 35%. Public trust is positively impacted by organizational performance at 63%, while community satisfaction is positively impacted at 76%. Additionally, there is a 44% positive correlation between public trust and community satisfaction. The study’s findings suggest that in order to boost public trust, organizational performance and community satisfaction must both be addressed.